Therapeutic effect of al-Quran murattal on anxiety, sFlt-1, PIGF and sFlt-1/PIGF ratio in pregnant women with risk of preeclampsia - Mamlukah, Mamlukah; Hadisaputro, Soeharyo; Soejoenoes, Ariawan; Shaluhiyah, Zahroh; Syukur, M. Amin (International Journal of Research in Medical Sciences, 2019)
Background: Pregnancy was a critical period. This study aimed to examine the effect of murattal al-Quran therapy on the level of anxiety, sFlt-1, and PIGF level in pregnant women with preeclampsia risk. Methods: A quasi-experimental study was conducted in February, 2018. Ten participants received routine midwifery care were combined with murattal of the Qur'an therapy, the rests as control group. Variables were measured at pre and post 12 interventions. Interviews were conducted after the intervention. Results: There was a mean difference of anxiety of 5.250 (SD of 11.021, 95% CI: 0.092-10,408, p-0.046), sFlt-1 p=0.411, PIGF p=0.002, sFlt-1/PIGF ratio p=0.001. Conclusions: This study found a decrease in the level of anxiety, increase score of PIGF and decrease of sFlt-1/PIGF ratio among pregnant women with the risk of preeclampsia who received routine midwifery care plus al-Quran Murattal therapy.